Corrosion Inhibition of Laser Welded Mg AZ31B-H24 Alloy in NaCl Medium Using Pectin as an Eco-Friendly Inhibitor - Balaji Viswanadhapalli; Bupesh Raja V K; Saranaya Jagadeesan (International Journal of Integrated Engineering, 2024)
A magnesium alloy material possesses properties like stiffness, strength, chemical activity, good machinability, etc. which loses its corrosion resistance caused by the chemical activity of active magnesium. To control the corrosion of magnesium AZ31B-H24 alloy, an eco-friendly, water-soluble, cheap, and readily available inhibitor like pectin can be used as an inhibitor in a 5% NaCl medium. To confirm the adsorption of inhibitor molecules on the metal surface, weight loss and surface studies (SEM) were carried out. In addition, the Langmuir adsorption isotherm also confirms the presence of a monolayer on the magnesium surface. The results revealed that the pectin molecules acted as an efficient inhibitor for both welded and non-welded specimens of Mg alloy.